2018
DOI: 10.1080/1828051x.2018.1443288
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of milk protein, fat, lactose, total solids and amino acid profiles of three different buffalo breeds in Guangxi, China

Abstract: This study compared the milk protein, fat, lactose, total solids and amino acids (AA) profiles of Murrah buffalo, Nili-Ravi buffalo and crossbreed buffalo. Buffalo milk samples of Murrah (n ¼ 25), Nili-Ravi (n ¼ 20) and Triple-crossbred (n ¼ 23) were collected and milk protein, fat, lactose, total solids and 17 AA profiles were determined. Milk protein and total solids contents of Murrah buffalo were higher than those of Nili-Ravi buffalo (p < .05). The average milk protein, fat, lactose and total solids conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 8 publications
8
30
9
Order By: Relevance
“…During the cheese fermentation process, proteases from microorganisms degrade the proteins in milk and produce large amounts of peptides that can be further degraded into small peptides and FAAs (Niro et al, 2017;Moser et al, 2018). The concentration of different FAAs in cheese depends on the milk, starter, rennet, ripening conditions, and time of maturation (Tavaria et al, 2003;Tofalo et al, 2015;McCarthy et al, 2017;Zhou et al, 2018). Furthermore, FAAs are an important component in cheese.…”
Section: Amino Acids In the Cheesementioning
confidence: 99%
“…During the cheese fermentation process, proteases from microorganisms degrade the proteins in milk and produce large amounts of peptides that can be further degraded into small peptides and FAAs (Niro et al, 2017;Moser et al, 2018). The concentration of different FAAs in cheese depends on the milk, starter, rennet, ripening conditions, and time of maturation (Tavaria et al, 2003;Tofalo et al, 2015;McCarthy et al, 2017;Zhou et al, 2018). Furthermore, FAAs are an important component in cheese.…”
Section: Amino Acids In the Cheesementioning
confidence: 99%
“…Studies have found that the values for the composition (milk protein, milk fat, and total solids) of diverse buffalo milk are significantly different [ 2 ]. Meanwhile, milk protein and fat content in triple-crossbred buffalo is higher than Nili-Ravi buffalo, but lower than Murrah buffalo [ 4 ]. Milk traits among different breeds are different, and genetics is one of the main factors affecting milk quality [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al . reported the fat, protein, lactose and total solids contents in the milk of Murrah buffalo, Nili‐Ravi buffalo and triple‐crossbred buffalo (Murrah buffalo, Nili‐Ravi buffalo and local swamp buffalo) . However, little information has been reported on the change of milk yield and milk components from the representative domestic buffalo breeds in China throughout lactation.…”
Section: Introductionmentioning
confidence: 99%
“…8 Zhou et al reported the fat, protein, lactose and total solids contents in the milk of Murrah buffalo, Nili-Ravi buffalo and triple-crossbred buffalo (Murrah buffalo, Nili-Ravi buffalo and local swamp buffalo). 9 However, little information has been reported on the change of milk yield and milk components from the representative domestic buffalo breeds in China throughout lactation. Therefore, the objective of the present study was to determine and compare the physicochemical parameters, such as total solids, protein, fat, lactose, and ash contents, and pH value, of buffalo milk from four representative breeds in China (Murrah, Nili-Ravi, F 1 and F H ), and to determine how these parameters varied throughout lactation.…”
Section: Introductionmentioning
confidence: 99%